IDNLearn.com: Where curiosity meets clarity and questions find their answers. Our platform offers detailed and accurate responses from experts, helping you navigate any topic with confidence.
Sagot :
Answer:
1. (-3,-2)
2. (1, -7)
3. (1, 2.5)
4. No solution
Step-by-step explanation:
Number 1: Substitution
Plug y in to substitute and get
2x + (2x + 4) = -8
4x + 4 = -8
4x = -12
x = -3
Then plug into the y equation
y = 2(-3) + 4
y = -6 + 4
y = -2
(-3, -2)
Number 2: Elimination
Begin eliminating by crossing out same values
40x + 12y = -44
-2y = 14
Solve for y
-2y = 14
y = -7
Solve for x
40x + 12(-7) = -44
40x - 84 = -44
40x = 40
x = 1
(1, -7)
Number 3: Elimination
Add the two and get:
-3x + 2y = 2
6y = 15
Solve for y:
6y = 15
y = 5/2
Solve for x:
3x + 4(5/2) = 13
3x + 10 = 13
3x = 3
x = 1
(1, 2.5)
Number 4: Substitution
Solving for y to begin with:
4x - y = -3
-y = -3 - 4x
y = 3 + 4x
Then solve for y in the second system
-8x + 2y = 6
2y = 6 + 8x
y = 3 + 4x
Set equal to each other
3 + 4x = 4 + 4x
3 = 4
No solution
We value your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Find clear answers at IDNLearn.com. Thanks for stopping by, and come back for more reliable solutions.